Teaching language through literature: George Orwell’s ‘Shooting an Elephant’ in the EFL classroom - Molla Azizur Rahman (Universitas Syiah Kuala, 2019)
This article intends to show how an English language teaching material can be developed using a literary text. It is a qualitative study, and I have used the content analysis method. Here the first and the second paragraphs of the essay, “Shooting an Elephant” by George Orwell, are explored for bringing out potential linguistic features to be taught to undergraduate level students who learn English as a foreign language (hereafter, EFL). All the four basic skills of English language are emphasized in this teaching material. Different items like comprehension questions, guessing the meaning from the context, identification of phrases and identification of ironic expressions are set to develop and test students’ comprehension level. Items, like breaking up long sentences into smaller ones, changing sentences, rewriting sentences and writing paragraphs, are designed to develop the writing skill of the students. Similarly, items for developing listening and speaking skills of the learners are also retained in this material. It is shown that an essay can also be a potential source for developing language teaching material only if the selection is properly made. Further studies may test the effectiveness of the material for teaching both basic language skills and language areas.